Pengaruh Persepsi Kemudahan, Persepsi Manfaat, dan Persepsi Harga Terhadap Keputusan Belanja Pada Aplikasi Cumart Dengan Kepercayaan Pelanggan Sebagai Variabel Moderating - Catarina Cori Paramitha; Rezky Agung Setiawan (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2020)
E-commerce is one of the concepts that is quite developed in the field of information technology. The concept of E-commerce provides many conveniences and advantages when compared to the concept of e-commerce conventional shopping, including all the information that consumers want can be accessed more detailed, fast without being limited by place and time, and the transaction process can be done remotely easier. So that with the implementation of this system it will be very easy and more benefit many parties, both consumers and sellers. The purpose of this research is to produce a web-based application, the Cumart application. With The implementation of this system will greatly facilitate and benefit both consumers and consumers seller.